(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Choledocholithiasis is a significant issue in gallstone disease, and common bile duct (CBD) stones can cause serious complications. Objective: This retrospective study compared the outcomes of endoscopic retrograde cholangiopancreatography (ERCP) and laparotomic surgery for choledocholithiasis at a tertiary care facility. Methods: Thirty-eight patients were divided into two groups: Group 1 (n = 21) underwent ERCP, whereas Group 2 (n = 17) underwent open laparotomy with biliary drainage. Liver function tests, including bilirubin, thymol turbidity, alanine aminotransferase (ALT), and aspartate aminotransferase (AST) levels, were performed before and after the intervention. Results: In Group 1, serum bilirubin levels decreased significantly from 172.3 ± 2.21 μmol/L to 24.2 ± 0.97 μmol/L postoperatively (P < 0.001), with significant improvements in the thymol test, ALT, and AST (P < 0.05). Group 2 showed moderate, non-significant biochemical improvements. Group 1 experienced no complications, whereas one patient in Group 2 had partial failure of the biliary-enteric anastomosis. Patients in Group 1 had shorter hospital stays than those in Group 2. Conclusion: The results support that ERCP is the preferred initial treatment for CBD stones when technically feasible, leading to quicker liver recovery, fewer complications, and reduced hospital stays. Laparotomic surgery remains crucial when ERCP fails or in cases that are complex.